2018
DOI: 10.1080/2162402x.2018.1440931
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive activity of tumor-infiltrating myeloid cells in patients with meningioma

Abstract: Meningiomas WHO grade I and II are common intracranial tumors in adults that normally display a benign outcome, but are characterized by a great clinical heterogeneity and frequent recurrence of the disease. Although the presence of an immune cell infiltrate has been documented in these tumors, a clear phenotypical and functional characterization of the immune web is missing. Here, we performed an extensive immunophenotyping of peripheral blood and fresh tumor tissue at surgery by multiparametric flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 26 publications
5
22
0
Order By: Relevance
“…The following antibodies were used to characterize blood M-MDSCs in melanoma and meningioma (Pinton et al, 2018) patients: CD14-FITC, HLA-DR-APC and CD124 PE. As the down-regulation of HLA-DR and CD124 expression are important parameters to determine two subsets of M-MDSCs, it is important to use FMO controls to define HLA-DR and CD124 gates as shown in Figure 3.…”
Section: Determination Of M-mdscs Expression Level On Pbmcsmentioning
confidence: 99%
“…The following antibodies were used to characterize blood M-MDSCs in melanoma and meningioma (Pinton et al, 2018) patients: CD14-FITC, HLA-DR-APC and CD124 PE. As the down-regulation of HLA-DR and CD124 expression are important parameters to determine two subsets of M-MDSCs, it is important to use FMO controls to define HLA-DR and CD124 gates as shown in Figure 3.…”
Section: Determination Of M-mdscs Expression Level On Pbmcsmentioning
confidence: 99%
“…This finding parallels the concept that cellular environment modulates tumor biology. This process has been well demonstrated in a variety of pan-cancer 12,27 and central nervous system tumour studies 28 , and has been suggested in meningiomas [29][30][31] . Multiparameter flow cytometry studies have demonstrated a heterogenous composition of immune cells in meningiomas 29,31 .…”
Section: Discussionmentioning
confidence: 78%
“…More specifically, there was a variable degree of infiltrative macrophages with high phagocytic activity and, to a lesser extent, T-cells, Natural Killers, and few B-cells. Analysis of fresh meningioma tissue has demonstrated a large fraction of leukocyte infiltration consisting of macrophages with immunosuppressive activity 30 , which are more prevalent in grade II tumors. In our study, M1 macrophages were the most active cell fraction based on overall cytokine correlation.…”
Section: Discussionmentioning
confidence: 99%
“…As this receptor ligand is the target of several new drugs, further investigation into the predictive link between PD-L1 expression and therapeutic sensitivity is important. Indeed, based on evidence of their expression, other checkpoint inhibitors, such as those targeting TIM-3 or LAG-3 may be useful in treating (54,59).…”
Section: Expression/immunoprofilingmentioning
confidence: 99%